Composite protective film for negative electrode of all-solid-state lithium metal battery as well as preparation method and application of composite protective film
By constructing a composite protective film composed of a carbon substrate and high-performance fluoroplastic on the surface of the negative electrode of the lithium metal battery, problems such as poor interface contact and insufficient mechanical performance in the lithium metal battery are solved, and the cycle life and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510387045.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when constructing a protective film on the negative electrode surface of the lithium metal battery, there are problems such as poor interface contact, insufficient mechanical properties, low ionic conductivity, poor compatibility with solid electrolytes, and difficulty in suppressing lithium dendrites, which are particularly obvious in solid lithium metal batteries.
A composite protective film composed of a carbon substrate and high-performance fluoroplastic is used to create a synergistic effect between the two through specific preparation methods, improving interface contact, improving mechanical properties, optimizing ion transmission, enhancing compatibility with solid electrolytes, and inhibiting the puncture of lithium dendrites.
It significantly improves the cycle life, charge and discharge performance and energy density of lithium metal batteries, improves the rate performance and safety of the battery, and solves the multiple shortcomings of the protective film in solid-state lithium metal batteries.
Smart Images

Figure CN119905594A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite protective film for an anode of an all-solid-state lithium metal battery, and a preparation method and application thereof. Background Art
[0002] Lithium metal batteries are considered to be ideal candidates for the next generation of high-performance batteries due to their advantages such as high energy density and long cycle life. However, the lithium metal anode is prone to dendrite growth and dissolution during the charge and discharge process, leading to problems such as battery capacity decay and reduced safety performance.
[0003] At present, a variety of lithium metal battery negative electrode protection methods have been proposed, such as: Constructing a protective film: Constructing a protective film on the surface of the lithium metal negative electrode can inhibit the growth and dissolution of lithium dendrites. Commonly used protective film materials include polymers, inorganic compounds and solid electrolytes.
[0004] Optimizing electrode structure: Optimizing the structure of lithium metal anode can improve its ability to inhibit lithium dendrite growth. Common structural modification methods include nano-sizing, 3D printing and composite materials.
[0005] The existing technology has the following defects and deficiencies in constructing a protective film on the surface of a lithium metal negative electrode, especially when applied to solid-state lithium metal batteries: (1) Poor interface contact: The interface contact between the solid electrolyte and the lithium metal anode is a key challenge for solid-state batteries. Traditional protective films, especially those simply coated with a layer of polymer or inorganic material, have difficulty in forming good wettability and adhesion at the solid-solid interface, resulting in high interface impedance and obstructed ion transport, which seriously affects the battery's cycle performance and rate performance. This is a prominent problem that does not exist in liquid batteries because the liquid electrolyte can well infiltrate the electrode surface.
[0006] (2) Insufficient mechanical properties: The volume of lithium metal changes greatly during the charge and discharge process. Traditional protective films often have insufficient mechanical strength and are prone to cracking and peeling during the cycle, thus losing their protective function. Especially in solid-state batteries, the solid electrolyte itself limits the deformation space of the electrode, which places higher requirements on the mechanical properties of the protective film.
[0007] (3) Low ion conductivity: Many protective film materials, especially polymers, have low ion conductivity, which will hinder the transmission of lithium ions, resulting in increased internal resistance and polarization of the battery. In solid-state batteries, the ion conductivity is lower than that of liquid batteries, and the low conductivity of the protective film will further deteriorate the battery performance.
[0008] (4) Poor compatibility with solid electrolytes: Different solid electrolytes (such as oxides, sulfides, polymers, etc.) have different chemical properties and interface characteristics. Traditional protective films may be incompatible with specific solid electrolytes, leading to problems such as interface reactions and by-product generation, affecting the long-term stability of the battery.
[0009] (5) It is difficult to inhibit the penetration of lithium dendrites in solid electrolytes: Although solid electrolytes can inhibit the growth of lithium dendrites to a certain extent, they cannot completely prevent it. Once lithium dendrites break through the protective film and pierce the solid electrolyte, it will cause a battery short circuit. Therefore, the protective film needs to have a stronger ability to block lithium dendrite penetration, especially in the case of high compaction density of solid-state batteries.
[0010] (6) Complex preparation process: The preparation process of some protective films is complex and costly, which is not conducive to large-scale production and application.
[0011] The technical problem to be solved by the present invention is to provide a composite protective film which is simple to prepare and has good electrochemical stability and ionic conductivity, so as to improve the performance and life of an all-solid-state lithium metal battery. Summary of the invention
[0012] The purpose of the present invention is to provide a composite protective film for the negative electrode of an all-solid-state lithium metal battery, and a preparation method and application thereof. A composite protective film composed of carbon and high-performance fluoroplastics is constructed on the surface of the lithium metal negative electrode, which can effectively inhibit the growth and dissolution of lithium dendrites and improve the cycle life, charge and discharge performance and energy density of the battery.
[0013] The objective of the present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a composite protective film for an anode of an all-solid-state lithium metal battery, comprising a carbon substrate and a high-performance fluoroplastic.
[0014] As some specific embodiments of the present invention, the carbon substrate includes at least one of carbon nanotubes (CNT), vapor-grown carbon fibers (VGCF), and graphite. Preferably, the carbon substrate is a carbon nanotube.
[0015] As some specific embodiments of the present invention, the high-performance fluoroplastic includes at least one of chlorinated polyvinylidene fluoride (PCTFE, also known as polychlorotrifluoroethylene), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), fluorinated alkyl modified PVDF, vinyl modified PVDF, and silane coupling agent modified PVDF.
[0016] As some specific embodiments of the present invention, the fluorinated alkyl-modified PVDF is an alkyl side chain containing fluorine atoms introduced into the PVDF molecular chain, including but not limited to trifluoromethyl (-CF3) and pentafluoroethyl (-C2F5); the fluorinated alkyl-modified PVDF is prepared by a solution blending method, wherein polyvinylidene fluoride PVDF and a fluorinated alkyl polymer or an additive containing a fluorinated alkyl functional group are dissolved in a co-solvent DMF or NMP, and the solvent is evaporated after sufficient mixing to uniformly mix the polymer components, thereby obtaining a fluorinated alkyl-modified PVDF composite material.
[0017] As some specific embodiments of the present invention, the vinyl-modified PVDF is to introduce a side group or chain segment containing a vinyl group (-CH=CH2) into the PVDF molecular chain; the vinyl-modified PVDF is prepared by a copolymerization method, in which a vinylidene fluoride (VDF) monomer is copolymerized with a vinyl-containing monomer, thereby directly introducing a vinyl group into the PVDF molecular chain.
[0018] As some specific embodiments of the present invention, the silane coupling agent modified PVDF is a composite material or surface-modified PVDF obtained by treating or modifying polyvinylidene fluoride (PVDF) with a silane coupling agent; the silane coupling agent modified PVDF is prepared by a solution blending method, wherein PVDF is dissolved in a solvent (such as DMF and / or NMP), a silane coupling agent is added to the PVDF solution, the mixture is stirred and mixed evenly, and the solvent is evaporated to obtain a silane coupling agent modified PVDF composite membrane. The silane coupling agent modification does not directly change the molecular chain structure of PVDF, but chemically or physically adsorbs the silane coupling agent on the surface of PVDF, or connects the silane coupling agent to the PVDF molecule through a grafting reaction.
[0019] As some specific embodiments of the present invention, the thickness of the composite protective film is 500 nm-50 μm.
[0020] As some specific embodiments of the present invention, the mass ratio of the carbon substrate to the high-performance fluoroplastic is 1:6-6:1.
[0021] When the composite protective film is less than 500 nm, the protective film thickness is too small to effectively prevent harmful substances in the electrolyte from contacting the negative electrode, resulting in negative electrode corrosion, capacity decay and shortened cycle life. When the composite protective film is higher than 50 μm, the protective film thickness is too large, which will increase the barrier distance of lithium ion transmission and reduce the charge and discharge efficiency of the battery; if the protective film thickness is too large, it will also occupy the internal space of the battery and reduce the energy density of the battery.
[0022] In a second aspect, the present invention provides a method for preparing a composite protective film as described in any one of the above, comprising the following steps: S1, dispersing the carbon substrate in an organic solvent to form a carbon substrate dispersion; S2, dissolving the high performance fluoroplastic in an organic solvent to form a fluoroplastic solution; S3, mixing the carbon substrate dispersion and the fluoroplastic solution to form a slurry; S4. Coating the slurry on the surface of the lithium metal negative electrode, and forming a composite protective film on the surface of the lithium metal negative electrode after drying and curing.
[0023] As some specific embodiments of the present invention, in step S1 or step S2, the organic solvent includes at least one of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), γ-butyrolactone, tetrachloroethylene and N,N-dimethylformamide (DMF).
[0024] As some specific embodiments of the present invention, in step S1, the mass volume concentration of the carbon substrate in the carbon substrate dispersion is 0.1 g / mL-1.5 g / mL.
[0025] As some specific embodiments of the present invention, in step S2, the mass volume concentration of the high performance fluoroplastic in the fluoroplastic solution is 0.1 g / mL-1 g / mL.
[0026] As some specific embodiments of the present invention, in step S1, the carbon substrate is added to the organic solvent, and the carbon substrate is uniformly dispersed in the organic solvent by ultrasonic oscillation to form a carbon substrate dispersion. Further, the power of the ultrasonic oscillation is 50-300 W, the time is 15-60 min, and the ultrasonic oscillation is performed in an intermittent operation mode, and the ultrasonic oscillation is stopped for 1 min every 5 min.
[0027] As some specific embodiments of the present invention, in step S1, the carbon substrate is added to an organic solvent and dispersed by a high-speed disperser, a high-speed stirrer or a homogenizer at a speed of 1000 rpm-2000 rpm for 30 min-60 min to form a carbon substrate dispersion.
[0028] As some specific embodiments of the present invention, in step S2, a high-performance fluoroplastic is added to an organic solvent, and stirred at a speed of 100-500 rpm for 2-12 h using a magnetic stirrer in a water bath or oil bath at 50-90°C until the high-performance fluoroplastic is completely dissolved in the organic solvent to form a fluoroplastic solution.
[0029] As some specific embodiments of the present invention, in step S3, when the carbon substrate dispersion and the fluoroplastic solution are mixed, a magnetic stirrer is used to stir at a speed of 100-400 rpm for 30-120 min, or a high-speed disperser is used to stir at a speed of 1000rpm-2000 rpm for 30 min-60 min to make them uniformly mixed.
[0030] As some specific embodiments of the present invention, in step S4, the drying method is selected from vacuum drying or normal pressure drying, preferably vacuum drying; the drying conditions include: temperature 40°C-120°C, preferably 60°C-100°C, time 2-24h, preferably 4-12h.
[0031] As some specific embodiments of the present invention, in step S4, the curing conditions include: temperature 100-200° C., preferably 120-180° C.; time 1-12 h, preferably 2-6 h.
[0032] In a third aspect, the present invention provides an all-solid-state lithium metal battery negative electrode, wherein the material of the negative electrode is metallic lithium or a metallic lithium complex, and a composite protective film as described in any one of the above items or a composite protective film prepared by any one of the above preparation methods is constructed on its surface.
[0033] In a fourth aspect, the present invention provides an all-solid-state lithium metal battery, comprising the all-solid-state lithium metal battery negative electrode described above.
[0034] As some specific embodiments of the present invention, the all-solid-state lithium metal battery also includes a positive electrode, and the positive electrode is selected from any one of lithium cobalt oxide, lithium nickel oxide, nickel cobalt manganese ternary material, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based material, lithium manganese oxide, lithium nickel manganese oxide, ferroferric oxide, and lithium titanate.
[0035] As some specific embodiments of the present invention, the all-solid-state lithium metal battery further includes a solid electrolyte, and the solid electrolyte includes at least one of a sulfide electrolyte, an oxide electrolyte and a polymer electrolyte.
[0036] In the prior art, there are studies on combining inorganic ceramics with polymers for lithium metal negative electrode protective films, most of which are aimed at liquid electrolyte systems. The formation of SEI film in liquid battery systems depends on the decomposition of electrolytes. In solid-state batteries, due to the lack of liquid electrolytes, the formation mechanism of SEI film is completely different. Therefore, it is not feasible to simply apply the experience in liquid batteries to solid-state batteries. This application optimizes the ratio, preparation process, etc. of carbon materials and high-performance fluoroplastics in view of the special environment of solid-state batteries to adapt to the characteristics of solid-solid interfaces and solid electrolytes, and overcomes the technical barriers from liquid to solid.
[0037] (1) Synergistic effect and technical effect: This application combines carbon materials with high-performance fluoroplastics, not by simple physical mixing, but by using a specific preparation method to produce a synergistic effect between the two.
[0038] (2) Improved interface contact: Carbon materials (such as carbon nanotubes, carbon fibers, etc.) have high conductivity and good flexibility, and can serve as a "bridge" to connect the lithium metal anode and the solid electrolyte, improve interface contact, and reduce interface impedance. High-performance fluoroplastics can provide good adhesion and film-forming properties, allowing the protective film to be tightly bonded to the electrode surface. The combination of the two can effectively solve the problem of poor interface contact in solid-state batteries.
[0039] (3) Improving mechanical properties: Carbon materials can enhance the mechanical strength and flexibility of the protective film, enabling it to better withstand the volume changes of lithium metal during the charging and discharging process and prevent cracking and peeling. High-performance fluoroplastics can provide a certain degree of elasticity to buffer the stress caused by electrode deformation. The combination of the two can significantly improve the mechanical properties of the protective film and extend the cycle life of the battery.
[0040] (4) Optimizing ion transport: The high conductivity of carbon materials can promote the transport of electrons, and the polar groups in high-performance fluoroplastics can interact with lithium ions to promote the transport of lithium ions. By optimizing the type, content and distribution of carbon materials, the ionic conductivity of the protective film can be further improved and the internal resistance of the battery can be reduced.
[0041] (5) Inhibiting lithium dendrite penetration: The high strength of carbon materials and the density of high-performance fluoroplastics can jointly block the penetration of lithium dendrites and improve the safety of batteries.
[0042] In summary, this application targets the special needs of solid-state lithium metal batteries by cleverly combining carbon materials with high-performance fluoroplastics, overcoming the shortcomings of the prior art in terms of solid-solid interface contact, mechanical properties, ionic conductivity, compatibility with solid electrolytes, and inhibition of lithium dendrite penetration.
[0043] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention constructs a composite protective film on the negative electrode of a lithium metal battery, which can provide a stable transmission channel for lithium ions, homogenize the migration rate of lithium ions, adjust the concentration distribution of lithium ions on the electrode surface, and achieve uniform lithium metal deposition / stripping.
[0044] (2) The present invention can significantly improve the solid-solid interface contact and reduce the interface impedance in the solid-state lithium metal battery through the synergistic effect of the carbon substrate and the high-performance fluoroplastic. The synergistic effect of the carbon substrate and the high-performance fluoroplastic can significantly improve the interface contact between the lithium metal negative electrode and the solid electrolyte, forming a low-impedance ion transmission channel. This effect cannot be achieved by simply mixing the carbon material and the fluoroplastic, but requires a specific preparation method and ratio to achieve good interface bonding and synergy between the two. The realization of such low interface impedance can significantly improve the rate performance and energy density of the solid-state battery. The carbon substrate (such as carbon nanotubes, carbon fibers) has high conductivity and flexibility, and can fill the gaps between the solid-solid interface to form a conductive path; the high-performance fluoroplastic provides good adhesion and film-forming properties, so that the protective film is tightly combined with the electrode and electrolyte surfaces. The synergistic effect of the two overcomes the problem of poor interface contact in solid-state batteries, which is difficult to achieve with conventional protective films.
[0045] (3) The composite protective film of the present invention has high mechanical properties and can better adapt to the harsh environment of solid-state batteries. The combination of the high strength of the carbon substrate and the flexibility of the high-performance fluoroplastic not only improves the overall mechanical strength of the protective film, but also gives it excellent fatigue resistance. This fatigue resistance is crucial to cope with the repeated volume changes of lithium metal during the charging and discharging process, and can significantly improve the cycle stability of the battery. The carbon substrate plays the main mechanical support role, preventing the protective film from breaking under stress; the high-performance fluoroplastic provides buffering and deformation capabilities, absorbs the stress caused by the volume change of the electrode, and prevents damage caused by stress concentration. The synergistic effect of the two enables the protective film to work stably and for a long time in the harsh environment of solid-state batteries.
[0046] (4) The composite protective film of the present invention can synergistically optimize the transport of electrons and ions in solid-state lithium metal batteries. The high conductivity of the carbon substrate combined with the affinity of the polar groups in the high-performance fluoroplastics for lithium ions not only achieves the rapid transport of electrons and ions, but also may form special ion transport channels at the interface, further reducing the ion transport impedance, thereby significantly improving the rate performance of the battery, especially the charge and discharge performance at high current density. The carbon substrate constructs an electron transport network, and the high-performance fluoroplastics interact with lithium ions through their polar groups to promote the migration of lithium ions. The synergistic effect of the two achieves the synergistic and efficient transport of electrons and ions, and improves the power density of the battery.
[0047] (5) The composite protective film of the present invention more effectively inhibits the penetration and growth of lithium dendrites in the solid electrolyte, which is crucial to achieving high performance, long cycle life and safety of lithium metal batteries. The growth of lithium dendrites is the root cause of the capacity decay and safety problems of lithium metal batteries. The present application combines a high-strength carbon substrate with a dense high-strength fluoroplastic matrix to form a multiple barrier mechanism, which can not only inhibit the lateral growth of lithium dendrites, but also effectively prevent their longitudinal penetration, and maintain good safety even at higher current densities. The high strength of the carbon substrate provides a physical barrier to prevent the growth of lithium dendrites; the density of the high-strength fluoroplastic reduces the diffusion channel of lithium ions and reduces the driving force for the growth of lithium dendrites. The synergistic effect of the two improves the ability of the protective film to inhibit the growth of lithium dendrites, thereby improving the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a cycle performance diagram of the lithium metal battery prepared in Example 1; Figure 2 This is the coulombic efficiency diagram of the lithium metal full battery prepared in Example 1; Figure 3 1 is a comparison chart of the cycle performance of the lithium metal battery of Example 1 and Comparative Example 1; Figure 4 This is a scanning electron microscope (SEM) image of the composite protective film prepared in Example 1; Figure 5 This is a scanning electron microscope (SEM) image of the composite protective film prepared in Comparative Example 2. DETAILED DESCRIPTION
[0049] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0050] Example 1 In this embodiment, a composite protective film is prepared on a lithium metal negative electrode, and the preparation steps are as follows: 1. Prepare lithium metal anode: A commercial lithium-copper composite strip (purchased from Tianjin Zhongneng Lithium Industry Co., Ltd.), i.e., a copper-lithium composite, was used as the negative electrode of the lithium metal battery.
[0051] 2. Preparation of CNT dispersion: Weigh 5 g of carbon nanotubes (CNTs), add 50 mL of N,N-dimethylformamide (DMF) into a beaker, slowly add CNTs into DMF, and oscillate with an ultrasonic power of 200 W for 30 minutes. Ultrasonicate for 5 minutes and stop for 1 minute until the CNTs are evenly dispersed in DMF to form a black and uniform CNT dispersion.
[0052] 3. Preparation of FEP solution: Weigh 25 g of tetrafluoroethylene-hexafluoropropylene copolymer (FEP), add 250 mL of N,N-dimethylformamide (DMF) into a beaker, slowly add FEP into DMF, and stir at 300 rpm using a magnetic stirrer in a water bath at 80°C for 2 hours until FEP is completely dissolved to form a transparent FEP solution.
[0053] 4. Mixing of CNT dispersion and FEP solution: The prepared CNT dispersion (50 mL) and FEP solution (250 mL) were mixed in a volume ratio of 1:5. The mass ratio of carbon-based carbon nanotubes (CNT) and high-performance fluoroplastic tetrafluoroethylene-hexafluoropropylene copolymer (FEP) was also 1:5.
[0054] The mixture was stirred at 400 rpm using a magnetic stirrer for 30 minutes to fully mix the mixture and form a uniform black slurry.
[0055] 5. Coating, drying and curing: (1) Coating: Use a coating machine to evenly coat the prepared slurry on the surface of the lithium metal negative electrode with a scraper. Adjust the gap between the scraper and the lithium metal negative electrode to control the film thickness to 20 μm.
[0056] (2) Drying: The coated lithium metal anode was placed in a vacuum drying oven and dried at 80°C under vacuum conditions for 8 hours to remove the solvent.
[0057] (3) Curing: The dried lithium metal anode is placed in a vacuum oven and cured at 150°C for 4 hours to form a dense network structure of FEP.
[0058] like Figure 4 The figure shows a scanning electron microscope image of the composite protective film prepared in Example 1. The surface of the composite protective film prepared in Example 1 is uniform and flat without obvious defects.
[0059] Example 2 In this embodiment, a composite protective film is prepared on a lithium metal negative electrode, and the preparation steps are as follows: 1. Prepare lithium metal anode: Commercial lithium copper composite tape (purchased from Tianjin Zhongneng Lithium Industry Co., Ltd.), i.e., copper-lithium composite is used as the negative electrode of lithium metal battery; 2. Preparation of CNT dispersion: Weigh 2.5 g of carbon nanotubes (CNTs), add 50 mL of N,N-dimethylformamide (DMF) into a beaker, slowly add CNTs into DMF, and use ultrasonic oscillation for 30 minutes with a power setting of 200 W until CNTs are evenly dispersed in DMF to form a black, uniform CNT dispersion. The ultrasonic process is intermittent, with 5 minutes of ultrasonication and 1 minute of rest to avoid overheating.
[0060] 3. Preparation of FEP solution: Weigh 15 g tetrafluoroethylene-hexafluoropropylene copolymer (FEP), add 150 mL N,N-dimethylformamide (DMF) into a beaker, slowly add FEP into DMF, and stir at 300 rpm in a constant temperature water bath at 80°C for 3 hours using a magnetic stirrer until FEP is completely dissolved to form a transparent FEP solution. A glass rod can be used to assist in stirring to accelerate dissolution.
[0061] 4. Mixing of CNT dispersion and FEP solution: The prepared CNT dispersion (50 mL) and FEP solution (150 mL) were mixed in a volume ratio of 1:3. The mass ratio of carbon-based carbon nanotubes (CNT) and high-performance fluoroplastic tetrafluoroethylene-hexafluoropropylene copolymer (FEP) was 1:6.
[0062] Use a magnetic stirrer to stir at 400 rpm for 60 minutes to fully mix the mixture and form a uniform black slurry. A glass rod can be used to assist in mixing during the stirring process to ensure uniformity.
[0063] 5. Coating, drying and curing: (1) Coating: Use a coating machine to evenly coat the prepared slurry on the surface of the lithium metal negative electrode. The wet film thickness is controlled by adjusting the gap between the scraper and the lithium metal negative electrode. The final film thickness after drying is about 20 μm.
[0064] (2) Drying: The coated lithium metal anode is placed in a vacuum drying oven and dried under vacuum conditions at 70°C for 10 hours to remove the solvent. Multiple vacuuming and nitrogen filling cycles can be performed during the drying process to more thoroughly remove the solvent.
[0065] (3) Curing: Place the dried lithium metal anode in a vacuum oven and cure it at 160°C for 3 hours to form a dense network structure of FEP. After curing, cool it naturally to room temperature.
[0066] Example 3 In this embodiment, a composite protective film is prepared on a lithium metal negative electrode, and the preparation steps are as follows: 1. Prepare lithium metal anode: A commercial lithium-copper composite strip (purchased from Tianjin Zhongneng Lithium Industry Co., Ltd.), i.e., a copper-lithium composite, was used as the negative electrode of the lithium metal battery.
[0067] 2. Preparation of CNT dispersion: Weigh 15 g of carbon nanotubes (CNTs) and add 100 mL of N,N-dimethylformamide (DMF) into a beaker. Slowly add CNTs into DMF and use ultrasonic oscillation for 45 minutes with a power of 250 W until the CNTs are evenly dispersed in DMF to form a black, uniform CNT dispersion. Perform intermittent operation during the ultrasonic process, and stop for 1 minute every 5 minutes to avoid overheating and solvent volatilization.
[0068] 3. Preparation of FEP solution: Weigh 2.5 g tetrafluoroethylene-hexafluoropropylene copolymer (FEP) and add 25 mL N,N-dimethylformamide (DMF) into a beaker. Slowly add FEP into DMF and stir at 400 rpm in a 90°C constant temperature oil bath using a magnetic stirrer for 4 hours until FEP is completely dissolved to form a transparent FEP solution.
[0069] 4. Mixing of CNT dispersion and FEP solution: The prepared CNT dispersion (100 mL) and FEP solution (25 mL) were mixed in a volume ratio of 4:1. The mass ratio of carbon-based carbon nanotubes (CNTs) and high-performance fluoroplastic tetrafluoroethylene-hexafluoropropylene copolymer (FEP) was 6:1.
[0070] A high-speed disperser was used to stir at a speed of 2000 rpm for 60 minutes to ensure that the high-concentration CNT dispersion and the FEP solution were fully mixed and uniformly formed into a uniform black slurry.
[0071] 5. Coating, drying and curing: (1) Coating: Use the scraper coating method to evenly coat the prepared slurry on the surface of the lithium metal negative electrode. The wet film thickness is controlled by adjusting the gap between the scraper and the lithium metal negative electrode or the spin coating parameters. The final film thickness after drying is about 20 μm.
[0072] (2) Drying: The coated lithium metal anode was placed in a vacuum drying oven and dried under vacuum conditions at 90 °C for 12 h to ensure that the solvent was completely removed.
[0073] (3) Curing: The dried lithium metal anode is placed in a vacuum oven and cured at 170 °C for 5 hours to form a dense network structure of FEP.
[0074] Example 4 In this embodiment, a composite protective film is prepared on a lithium metal negative electrode, and the preparation steps are as follows: 1. Prepare lithium metal anode: Commercial lithium-copper composite strip (Tianjin Zhongneng Lithium Industry Co., Ltd.), that is, copper-lithium composite, is used as the negative electrode of lithium metal battery.
[0075] 2. Preparation of VGCF dispersion: Weigh 5 g of vapor grown carbon fiber (VGCF) and add 50 mL of N-methylpyrrolidone (NMP) into a beaker.
[0076] Slowly add VGCF into NMP and use a high-speed disperser or homogenizer to disperse it at a speed of 1500 rpm for 45 minutes to evenly disperse VGCF in NMP to form a black uniform VGCF dispersion.
[0077] 3. Preparation of PCTFE solution: Weigh 25 g of chlorinated polyvinylidene fluoride (PCTFE) (purchased from Beijing Epsilon Technology Co., Ltd.) and add 250 mL of N-methylpyrrolidone (NMP) into a beaker.
[0078] PCTFE was slowly added into NMP, and stirred at 400 rpm for 2 hours using a magnetic stirrer on a constant temperature heating table at 70°C until PCTFE was completely dissolved to form a transparent PCTFE solution.
[0079] 4. Mixing of VGCF dispersion and PCTFE solution: The prepared VGCF dispersion (50 mL) and PCTFE solution (250 mL) were mixed at a volume ratio of 1:5. The mass ratio of carbon-based vapor-grown carbon fiber (VGCF) and high-performance fluoroplastic PCTFE was 1:5.
[0080] The mixture was stirred at 400 rpm using a magnetic stirrer for 45 minutes to fully mix the mixture and form a uniform black slurry.
[0081] 5. Coating, drying and curing: (1) Coating: The prepared slurry is evenly coated on the surface of the lithium metal negative electrode using a scraper coating method. The wet film thickness is controlled by adjusting the gap between the scraper and the lithium metal negative electrode. The final film thickness after drying is about 20 μm.
[0082] (2) Drying: The coated lithium metal anode was placed in a vacuum drying oven and dried at 90 °C for 10 hours to remove the solvent.
[0083] (3) Curing: Place the dried lithium metal anode in a vacuum oven and cure it at 160 °C for 5 hours to form a dense network structure of CTFE. After curing, cool it naturally to room temperature.
[0084] Example 5 In this embodiment, a composite protective film is prepared on a lithium metal negative electrode, and the preparation steps are as follows: 1. Prepare lithium metal anode: Commercial lithium-copper composite strip (Tianjin Zhongneng Lithium Industry Co., Ltd.), that is, copper-lithium composite is used as the negative electrode of lithium metal battery.
[0085] 2. Preparation of graphite dispersion: Weigh 5 g of graphite powder (natural graphite or artificial graphite) and add 50 mL of dimethyl sulfoxide (DMSO) into a beaker.
[0086] The graphite powder was slowly added into DMSO and dispersed using a high-speed stirrer at a rotation speed of 1000 rpm for 60 minutes to uniformly disperse the graphite in DMSO to form a black uniform graphite dispersion.
[0087] 3. Preparation of fluorinated alkyl modified PVDF solution: Weigh 25 g of fluorinated alkyl-modified PVDF and add 250 mL of dimethyl sulfoxide (DMSO) into a beaker.
[0088] The fluorinated alkyl-modified PVDF was slowly added to DMSO, and stirred at 300 rpm for 2 hours using a magnetic stirrer in a constant temperature water bath at 60°C until the fluorinated alkyl-modified PVDF was completely dissolved to form a transparent or slightly viscous solution.
[0089] 4. Mixing of graphite dispersion and fluorinated alkyl modified PVDF solution: The prepared graphite dispersion (50 mL) and fluorinated alkyl modified PVDF solution (250 mL) were mixed in a volume ratio of 1:5, and the mass ratio of carbon-based graphite powder and high-performance fluoroplastic fluorinated alkyl modified PVDF was 1:5.
[0090] The mixture was stirred at 500 rpm using a magnetic stirrer for 30 minutes to fully mix the mixture and form a uniform black slurry.
[0091] 5. Coating, drying and curing: (1) The prepared slurry is evenly coated on the surface of the lithium metal negative electrode using a scraper coating method. The wet film thickness is controlled by adjusting the gap between the scraper and the lithium metal negative electrode. The final film thickness after drying is about 20 μm.
[0092] (2) Drying: The coated lithium metal negative electrode was placed in a vacuum drying oven and dried at 80°C for 9 hours to remove the solvent.
[0093] (3) Curing: Place the dried lithium metal anode in a vacuum oven and cure it at 150°C for 4.5 hours to form a dense network structure of the fluorinated alkyl-modified PVDF. After curing, cool it naturally to room temperature.
[0094] Example 6 This embodiment prepares a composite protective film on a lithium metal negative electrode. Compared with Example 1, the only difference is that the CNT in Example 1 is replaced with VGCF, and the other preparation steps and parameters are exactly the same as those in Example 1.
[0095] Example 7 This embodiment prepares a composite protective film on a lithium metal negative electrode. Compared with Example 1, the only difference is that the CNT in Example 1 is replaced with graphite, and the other preparation steps and parameters are exactly the same as those in Example 1.
[0096] Example 8 This embodiment prepares a composite protective film on a lithium metal negative electrode. Compared with Example 4, the only difference is that the VGCF in Example 4 is replaced by CNT, and the other preparation steps and parameters are exactly the same as those in Example 4.
[0097] Example 9 This embodiment prepares a composite protective film on a lithium metal negative electrode. Compared with Example 5, the only difference is that the graphite in Example 5 is replaced by CNT, and the other preparation steps and parameters are exactly the same as those in Example 5.
[0098] Comparative Example 1 This comparative example provides a lithium metal negative electrode without a composite protective film, and uses the same copper-lithium composite as in Example 1 as the lithium metal negative electrode, specifically a commercial lithium-copper composite strip purchased from Tianjin Zhongneng Lithium Industry Co., Ltd.
[0099] Comparative Example 2 In this comparative example, a composite protective film is prepared on a lithium metal negative electrode, and the preparation steps are as follows: 1. Prepare lithium metal anode: Commercial lithium-copper composite belt (purchased from Tianjin Zhongneng Lithium Industry Co., Ltd.) uses a copper-lithium composite as the lithium metal negative electrode.
[0100] 2. Preparation of CNT dispersion: Weigh 17.5 g of carbon nanotubes (CNTs) and add 175 mL of N,N-dimethylformamide (DMF) into a beaker.
[0101] Slowly add CNT into DMF and oscillate with ultrasonic power of 200 W for 30 minutes, ultrasonicate for 5 minutes and stop for 1 minute, until CNT is evenly dispersed in DMF to form a black uniform CNT dispersion.
[0102] 3. Preparation of FEP solution: Weigh 2.5 g of tetrafluoroethylene-hexafluoropropylene copolymer (FEP) and add 25 mL of N,N-dimethylformamide (DMF) into a beaker.
[0103] Slowly add FEP to DMF and stir at 300 rpm in a constant temperature water bath at 80 °C for 5 hours using a magnetic stirrer until FEP is dissolved as much as possible. A glass rod can be used to assist in stirring to accelerate dissolution.
[0104] 4. Mixing of CNT dispersion and FEP solution: The prepared CNT dispersion (175 mL) and FEP solution (25 mL) were mixed in a volume ratio of 7:1. The mass ratio of carbon-based carbon nanotubes (CNTs) and high-performance fluoroplastic tetrafluoroethylene-hexafluoropropylene copolymer (FEP) was 7:1.
[0105] Due to the extremely high CNT content, the slurry may be very viscous after mixing. Use a high-speed disperser to stir at 3000 rpm for 90 minutes to ensure that the high-concentration CNT dispersion and FEP solution are fully mixed and evenly formed into a uniform black slurry.
[0106] 5. Coating, drying and curing: (1) Use a coating machine to evenly coat the prepared slurry on the surface of the lithium metal negative electrode with a scraper. Adjust the gap between the scraper and the lithium metal negative electrode to control the film thickness to 20 μm.
[0107] (2) Drying: The coated lithium metal anode was placed in a vacuum drying oven and dried at 80°C under vacuum conditions for 8 hours to remove the solvent.
[0108] (3) Curing: The dried lithium metal anode is placed in a vacuum oven and cured at 150°C for 4 hours to form a dense network structure of FEP.
[0109] like Figure 5 Shown is a scanning electron microscope image of the composite protective film prepared in Comparative Example 2. It can be seen that obvious cracks appear on the surface of the composite protective film.
[0110] Comparative Example 3 In this embodiment, a composite protective film is prepared on a lithium metal negative electrode, and the preparation steps are as follows: 1. Prepare lithium metal anode: Commercial lithium-copper composite strip (Tianjin Zhongneng Lithium Industry Co., Ltd.), that is, copper-lithium composite is used as the negative electrode of lithium metal battery.
[0111] 2. Preparation of CNT dispersion: Weigh 2.14 g of carbon nanotubes (CNTs) and add 43 mL of N,N-dimethylformamide (DMF) into a beaker.
[0112] Slowly add CNT into DMF and oscillate with ultrasonic power of 200 W for 30 minutes, ultrasonicate for 5 minutes and stop for 1 minute, until CNT is evenly dispersed in DMF to form a black uniform CNT dispersion.
[0113] 3. Preparation of FEP solution: Weigh 15 g of tetrafluoroethylene-hexafluoropropylene copolymer (FEP) and add 150 mL of N,N-dimethylformamide (DMF) into a beaker.
[0114] Slowly add FEP to DMF and stir at 300 rpm in a 80°C water bath for 2.5 hours using a magnetic stirrer until FEP is completely dissolved to form a transparent FEP solution. A glass rod can be used to assist in stirring to accelerate dissolution.
[0115] 4. Mixing of CNT dispersion and FEP solution: The prepared CNT dispersion (43 mL) and FEP solution (150 mL) were mixed at a volume ratio of about 1:3.5, and the mass ratio of carbon-based carbon nanotubes (CNTs) and high-performance fluoroplastic tetrafluoroethylene-hexafluoropropylene copolymer (FEP) was 1:7.
[0116] Use a magnetic stirrer to stir at 450 rpm for 45 minutes to fully mix the mixture and form a uniform black slurry. A glass rod can be used to assist in mixing during the stirring process to ensure uniformity.
[0117] 5. Coating, drying and curing: (1) Use a coating machine to evenly coat the prepared slurry on the surface of the lithium metal negative electrode with a scraper. Adjust the gap between the scraper and the lithium metal negative electrode to control the film thickness to 20 μm.
[0118] (2) Drying: The coated lithium metal anode was placed in a vacuum drying oven and dried at 80°C under vacuum conditions for 8 hours to remove the solvent.
[0119] (3) Curing: The dried lithium metal anode is placed in a vacuum oven and cured at 150°C for 4 hours to form a dense network structure of FEP.
[0120] Comparative Example 4 In this comparative example, a composite protective film was prepared on a lithium metal negative electrode. Compared with Example 1, the only difference was that the type of carbon substrate was replaced by carbon nanotubes (CNT) with carbon nanospheres (purchased from Carbon Nanotechnologies, Inc). 2.5 g of carbon nanospheres were weighed, and the remaining steps were the same as in Example 1.
[0121] Comparative Example 5 In this comparative example, a composite protective film is prepared on a lithium metal negative electrode. Compared with Example 5, the only difference is the type of high-performance fluoroplastic. The high-performance fluoroplastic is replaced by conventional PVDF (purchased from Sigma-Aldrich) instead of fluorinated alkyl-modified PVDF in Example 5, and 25 g of conventional PVDF is weighed. The remaining steps are the same as in Example 5. Comparative Example 7 verifies the effect of using conventional PVDF instead of fluorinated alkyl-modified PVDF on the performance of the composite protective film.
[0122] Comparative Example 6 In this comparative example, a composite protective film without a carbon substrate is prepared on a lithium metal negative electrode, and the steps are as follows: 1. Prepare lithium metal anode: The same commercial lithium-copper composite strip as in Example 1 (purchased from Tianjin Zhongneng Lithium Industry Co., Ltd.) was used, that is, the copper-lithium composite was used as the negative electrode of the lithium metal battery.
[0123] 2. Prepare FEP solution (basically the same as step 3 of Example 1): Weigh 30 g of tetrafluoroethylene-hexafluoropropylene copolymer (FEP), add 300 mL of N,N-dimethylformamide (DMF) into a beaker, slowly add FEP into DMF, and stir at 300 rpm using a magnetic stirrer in a water bath at 80°C for 3 hours until FEP is completely dissolved to form a transparent FEP solution.
[0124] 3. Coating, drying and curing (basically the same as step 5 of Example 1): (1) Coating: Use a coating machine to evenly coat the prepared FEP solution on the surface of the lithium metal negative electrode with a scraper. Adjust the gap between the scraper and the lithium metal negative electrode to control the film thickness to 20 μm.
[0125] (2) Drying: The coated lithium metal anode was placed in a vacuum drying oven and dried at 80°C under vacuum conditions for 8 hours to remove the solvent.
[0126] (3) Curing: The dried lithium metal anode is placed in a vacuum oven and cured at 150°C for 4 hours to form a dense network structure of FEP.
[0127] Effect Example 1 Performance test: The lithium metal negative electrodes prepared in the above embodiments and comparative examples were assembled into lithium metal batteries, and the positive electrode was NCM811 (nickel-cobalt-manganese ternary positive electrode material) with a loading of 10 mg / cm per unit area. 2 The electrode is an electrolyte sheet made of 100 mgLi6PS5Cl pressed at 50 MPa.
[0128] In an inert gas glove box with a water and oxygen content of ≤0.01 ppm, the assembled lithium metal battery was charged and discharged once at a rate of 0.1 C, and then the charge and discharge cycle test was performed at a rate of 1 C. The first efficiency (the first charge and discharge coulomb efficiency) and the capacity retention rate after the cycle were tested respectively, and the results are shown in Table 1 below.
[0129] Table 1 Performance test results of lithium metal batteries
[0130] It can be seen from Table 1 that using the composite protective film of the present invention to protect the lithium metal negative electrode can enable the lithium metal battery to exert a higher first effect, have a better capacity retention rate, and improve the rate performance of the lithium ion battery.
[0131] Figure 1 This is a cycle performance diagram of the lithium metal battery prepared in Example 1. Figure 2 This is the coulombic efficiency diagram of the lithium metal full battery prepared in Example 1. It can be seen that when the composite protective film prepared by the present invention is used for lithium metal negative electrode protection, the lithium metal battery can obtain excellent cycle ability and capacity retention rate.
[0132] 1. Figure 3 It is a comparison chart of the cycle performance of the lithium metal battery of Example 1 and Comparative Example 1. Compared with the lithium metal battery made of conventional lithium negative electrode in Comparative Example 1, the cycle performance of the lithium metal battery of the present invention is significantly improved after applying a composite protective film on its surface.
[0133] 2. Comparing Examples 1-3 with Comparative Examples 2 and 3, it can be seen that the mass ratio of carbon material to high-performance fluorine material is crucial to the performance of the composite protective film. Too high or too low a ratio will lead to performance degradation. The preferred mass ratio range of the two is 1:6-6:1. This range is not set arbitrarily, but is based on a comprehensive consideration of material properties and synergistic effects.
[0134] Figure 4 This is a scanning electron microscope (SEM) image of the composite protective film obtained in Example 1. Figure 5 The scanning electron microscope (SEM) image of the composite protective film prepared in Comparative Example 2 is shown in FIG. Figure 4 and Figure 5It can be seen that the surface of the composite protective film prepared in Example 1 is uniform and flat without obvious defects; while the surface of the composite protective film prepared in Comparative Example 2 has obvious cracks.
[0135] When the carbon material content is too high, such as in Comparative Example 2, where the mass ratio of the carbon substrate to the high-performance fluoroplastic is 7:1, the composite protective film may have the following problems: (1) Poor dispersibility: Carbon materials tend to agglomerate and are difficult to form a uniform and stable dispersion, especially at high concentrations. This will result in an uneven film layer after coating, affecting its performance.
[0136] (2) Poor film-forming property: The content of high-performance fluorine materials is relatively insufficient, and a continuous and dense film cannot be formed. The film layer is prone to cracking and peeling, resulting in the failure of the protective effect.
[0137] (3) Poor mechanical properties: The film layer is very brittle and cannot withstand the volume change of lithium metal during the charging and discharging process, and is prone to mechanical failure.
[0138] (4) Poor interface contact: Due to poor film forming properties, the interface contact between the protective film and the lithium metal negative electrode and solid electrolyte is poor, resulting in increased interface impedance and affecting ion transport.
[0139] (5) Poor electrochemical performance: Due to the above problems, the cycle performance and rate performance of the battery will be seriously affected. As shown in Table 1, the first efficiency, number of cycles and capacity retention rate of Comparative Example 2 are significantly lower than those of Examples 1-3.
[0140] When the content of high-performance fluorine material is too high, such as in Comparative Example 3, where the mass ratio of carbon substrate to high-performance fluorine plastic is 1:7, the composite protective film has the following problems: (1) Poor conductivity: The carbon material content is relatively insufficient, making it difficult to form an effective conductive network, resulting in obstructed electron transmission and increased interface impedance.
[0141] (2) Insufficient mechanical strength: The reinforcement effect provided by carbon materials is limited, the mechanical strength and fatigue resistance of the film layer are poor, and it cannot effectively inhibit the penetration of lithium dendrites.
[0142] (3) The interface contact may be poor: Although the high-performance fluorine material has good film-forming properties, the interface contact is not as good as that of Examples 1-3 due to the lack of sufficient carbon material to fill the interface gaps.
[0143] (4) Limited electrochemical performance: Due to the lack of conductivity and mechanical properties, the cycle performance and rate performance of the battery are affected. As shown in Table 1, the first efficiency, number of cycles and capacity retention rate of Comparative Example 3 are significantly lower than those of Examples 1-3.
[0144] When the mass ratio of carbon substrate to high-performance fluoroplastic is in the range of 1:6-6:1, carbon material and high-performance fluoroplastic can exert the best synergistic effect, thus obtaining excellent comprehensive performance: (1) Good dispersibility and film-forming properties: An appropriate amount of carbon material can be evenly dispersed in the high-performance fluorine material matrix to form a uniform and dense film.
[0145] (2) Excellent mechanical properties: The carbon material enhances the mechanical strength and fatigue resistance of the film layer, enabling it to better withstand the volume changes of lithium metal.
[0146] (3) Good interface contact: The carbon material fills the interface gaps, and the high-performance fluorine material provides good adhesion, which together improves the interface contact and reduces the interface impedance.
[0147] (4) Excellent electrochemical performance: Good conductivity, mechanical properties and interface contact jointly promote the transport and uniform deposition / stripping of lithium ions, thereby improving the cycle performance and rate performance of the battery.
[0148] 3. According to Table 1, the lithium metal batteries of Examples 4-7 have higher battery cycle performance and capacity retention rate, while other groups of embodiments have better performance. In the technical solution of the present invention, carbon nanotubes are used as the preferred carbon substrate. When the composite protective film is prepared together with high-performance fluoroplastics, the lithium metal battery can have higher battery cycle performance and capacity retention rate. Other types of carbon substrates also fall within the protection scope of the present invention.
[0149] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A composite protective film for an all-solid-state lithium metal battery negative electrode, characterized in that: Includes carbon substrates and fluoroplastics; The carbon substrate includes at least one of carbon nanotubes and gas-generated carbon fibers; The fluoroplastic includes at least one of chlorinated polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, fluorinated alkyl modified PVDF, vinyl modified PVDF, and silane coupling agent modified PVDF; The mass ratio of the carbon substrate to the fluoroplastic is 1:6-6:
1.
2. The composite protective film according to claim 1, characterized in that: The thickness of the composite protective film is 500 nm-50 μm.
3. A method for preparing a composite protective film according to claim 1 or 2, characterized in that: The steps include: S1, dispersing the carbon substrate in an organic solvent to form a carbon substrate dispersion; S2, dissolving the fluoroplastic in an organic solvent to form a fluoroplastic solution; S3, mixing the carbon substrate dispersion and the fluoroplastic solution to form a slurry; S4. Coating the slurry on the surface of the lithium metal negative electrode, and forming a composite protective film on the surface of the lithium metal negative electrode after drying and curing.
4. The preparation method according to claim 3, characterized in that: The organic solvent includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, γ-butyrolactone, tetrachloroethylene and N,N-dimethylformamide.
5. The preparation method according to claim 3, characterized in that: In step S1, the mass volume concentration of the carbon substrate in the carbon substrate dispersion is 0.1 g / mL-1.5 g / mL; And / or, in step S2, the mass volume concentration of the fluoroplastic in the fluoroplastic solution is 0.1 g / mL-1 g / mL.
6. An all-solid-state lithium metal battery negative electrode, characterized in that: The material of the negative electrode is metallic lithium or a metallic lithium composite, and a composite protective film as claimed in claim 1 or 2 or a composite protective film prepared by the preparation method as claimed in any one of claims 3 to 5 is constructed on the surface of the negative electrode.
7. An all-solid-state lithium metal battery, characterized in that: Comprising the all-solid-state lithium metal battery negative electrode as claimed in claim 6; It also includes a positive electrode and a solid electrolyte, wherein the positive electrode is selected from any one of lithium cobalt oxide, lithium nickel oxide, nickel cobalt manganese ternary material, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based material, lithium manganese oxide, lithium nickel manganese oxide, ferroferric oxide, and lithium titanate; The solid electrolyte includes at least one of a sulfide electrolyte, an oxide electrolyte, and a polymer electrolyte.
Citation Information
Patent Citations
Lithium metal negative electrode, preparation method thereof and lithium metal battery
CN111490250A
Lithium metal protective layer and preparation method thereof and battery with protective layer
CN111490252A